Semar’s Philosophy as a Proposed Code of Ethics for the Profession of Educator Accountant - Yulianti Raharjo; Tjiptohadi Sawarjuwono (Universitas Hayam Wuruk Perbanas, 2022)
The art of wayang kulit (puppit) is one of the original local wisdoms of Indonesia that has been embedded in the culture of the Javanese people for a long time. Each character in wayang kulit has a unique characteristic and a very deep meaning because it provides an overview of life. One example is Semar. Semar is described as a religious, strong, and wise teacher and leader. His behavior reflects the overall human capacity, both in thinking and in choosing an action or decision. This study aims to examine Semar’s philosophy which is used as a proposal in the preparation of a code of ethics for the profession of educator accountants. By using the library research method, this study seeks to examine various literatures obtained from previous studies and books related to Semar’s philosophy to get an overview of the characteristics of Semar and educator accountants. The results of this study conclude that Semar is a simple figure with various unique characteristics. He can be a role model in living life, including being religious, wise, intelligent, honest, earnest, loyal, thorough, never hesitate, professional, and public-oriented. This research is expected to be used as a proposal to the Indonesian Institute of Accountants – IAI and related regulators in compiling a professional code of ethics as a guide for the profession of educator accountant.